Consumer Awareness Towards Ayurveda Products and the Factors Influencing Choice of Ayurveda Products - Ghalawat, Suman; Mehla, Sunita; Malik, Joginder Singh; Goyal, Megha (Indian Journal of Extension Education, 2019)
Ayurveda is basically a natural way to preserve health of an individual through conserving the folks mind, body and spirit practiced equability with nature. The goal of the current paper was to study the reasons of preferring Ayurveda products and to determine the factors affecting ayurvedic products. Convenience sampling was used. Data has been collected from 100 customers who used ayurvedic products and purchased either from local shops, retail shops and online as well were selected for the study during January to March 2019 from the Hisar city of Haryana District. Factor analysis and average has been used to identify factors influencing selection of ayurvedic products while using SPSS 13. The survey data from the questionnaire was analyzed using factor analysis in order to summarize the 10 statements related to relevance of ayurvedic medicines into smaller sets. These 10 statements are reduced to four principal components through varimax rotation. The percentage of variance explained by factor 1 to 4 was 18.412, 18.004, 16.579 and 13.042. Study revealed that effects of ayurvedic medicine and use of ayurvedic medicine has high Cronbach alpha value i.e. .562 and .550 respectively. Hence it can be concluded that ayurvedic medicine along with allopathic, homeopathic medicine is good for common diseases. Moreover, ayurvedic medicines should be taken under doctor’s prescription as everyone is concerned about their health and moving towards the ayurvedic or nature based products. Even though, ayurvedic medicines too have side effects on our health if taken without supplements.
Keywords: Allopathic; Ayurveda; Equability; Homeopathic; Impact; Medicine